PENGEMBANGAN SITU CIPANTEN BERBASIS EKOWISATA DI KABUPATEN MAJALENGKA - Riyanti, Anti; Afriza, Lia (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2019)
Majalengka has a variety of tourist destinations that attract local and foreign tourists. Majalengka as a tourist gateway to West Java which has the potential to attract tourists by optimizing its Tourism Destination Areas. Diversity of Tourism Attractions in Majalengka has different thematic, one of which is Situ Cipanten which has the character of development ready for sale. Based on this background, the purpose of this study is to determine the existing condition of Cipanten Situ Tourism Attraction in Majalengka and the development of Cipanten Situ Tourism Attraction in Majalengka. The research method used is descriptive method with inductive analysis, so that this study can describe the object of research systematically and accurately. Based on the data source, the data collection uses primary and secondary sources. The results show the potential of Gunung Kuning Village has a tourist attraction (DTW) of a lake named Situ Cipanten. The main products in Situ Cipanten are lakes or situ which have seven springs surrounded by nature which are preserved by the environment, there are 7 springs in Situ Cipanten DTW and Patilasan Siliwangi where the horses are placed in Situ Cipanten. However, due to lack of management, this makes the site untreated and few visitors come. In conclusion, by developing this region, it can create thematic greening. Development of attractions such as the use of lakes and the use of surrounding forests for educational tourism (there are names of trees with various types of plants). Uniformity of the theme of the development of tourist attraction on the basis of ecotourism must also exist so that it can cause its own uniqueness.